The fundamental role of the education inspectorate in improving educational and career guidance processes - Teruel Naval, Rut; Ortiz Ballester, Elena (Avances en Supervisión Educativa, 2024)
This article analyzes the role of teachers and educational and professional guidance services in counselling, with special emphasis on vocational training courses, as well as the key role of the education inspectorate.The Organic Law 2/2006, of May 3, as amended by Organic Law 3/2020, establishes guidance as a fundamental principle of the Spanish educational system, linking it to the comprehensive education of students and the reduction of school dropout rates. The article identifies major challenges facing educational and professional guidance in Spain: the reduction of school dropout, the mismatch between educational offerings and labor market demands, and the accreditation of professional skills. It examines the current regulations and the role of the education inspectorate in its improvement. Finally, it proposes specific actions of the education inspectorate to contribute to a more equitable, personalized and student-centered educational system.
Keywords: Academic and vocational guidance; basic education; vocational education and training; school dropout; actions of the inspectorate of education